Use of a physiologically based extraction test to estimate the human bioaccessibility of potentially toxic elements in urban soils from the city of Glasgow, UK - Sialelli, Julien; Urquhart, Graham J; Davidson, Christine M; Hursthouse, Andrew S (Environmental geochemistry and health, 2010)
A simple, two-stage, physiologically based extraction has been applied to assess the human bioaccessibility of potentially toxic elements (PTE) in 20 urban soils from a major UK city. Chromium and iron bioaccessibilities were found to be markedly higher in the intestinal phase, whilst lead and zinc bioaccessibilities were higher in the stomach. Copper and manganese bioaccessibilities were generally similar under both extraction conditions. Principal component analysis was used to study relationships amongst bioaccessible element concentrations and land use. Distinctions could be observed between the distributions of the urban metals—copper, lead and zinc—and metals predominantly of geogenic origin, such as iron. There was no clear delineation between roadside soils and soils obtained from public parks. Bioaccessible analyte concentrations were found to be correlated with pseudototal (aqua regia soluble) analyte concentrations for all elements except iron. Results of the BCR sequential extraction did not, in general, provide a good indication of human bioaccessibility. Comparison of bioaccessible PTE concentrations with toxicological data indicated that lead is the element of greatest concern in these soils but that levels are unlikely to pose a health risk to children with average soil intake.